Maqasid Sharia and the Biomedical Ethics of E-Cigarettes: A Contemporary Islamic Legal Assessment - Nur Aqila Mohd Zahari; Mohd Hafiz Safiai (Faculty of Sharia, IAIN Metro, 2025)
This study critically examines the consumption of electronic cigarettes through the integrative lens of Maqasid al-Sharia, health preservation, and legal evaluation. Employing a qualitative methodology grounded in document analysis, this research draws upon a diverse array of primary and secondary sources, including authoritative fatwas, peer-reviewed medical literature, and official public health data. The study adopts a Maqasid-based ijtihad framework, supported by principles from Ushul Fiqh and qawaʿid fiqhiyyah, particularly the maxim al-darar yuzal (harm must be eliminated). Given that e-cigarettes are a modern phenomenon not clearly stated in classical Islamic texts, the issue falls under the domain of fiqh al-nawazil (the jurisprudence of novel occurrences), requiring contemporary legal reasoning (ijtihad mu'asir) to determine their ruling. The findings reveal a substantial incongruity between the use of electronic cigarettes and the core objectives of Maqasid al-Sharia, particularly the imperative to safeguard life (hifz al-nafs) and intellect (hifz al-ʿaql). Moreover, Islamic legal pronouncements on this matter vary, yet a growing corpus of contemporary fatwas aligns with a precautionary stance rooted in the principle of harm prevention. The study underscores that while e-cigarettes are often perceived as less harmful than conventional tobacco, their adverse health effects and potential to undermine societal welfare necessitate a reevaluation within Islamic ethical-legal frameworks. Limitations of the study include its reliance on secondary data and the evolving nature of medical consensus. These findings contribute to a nuanced interdisciplinary dialogue at the intersection of Islamic jurisprudence, public health, and ethical consumption.